Suppressive effects of Momordica charantia MAP30 on the senescence, proliferation and migration of bladder cancer cells mediated by CENPA - Kun Lu; Liu Chao; Jin Wang; Xiangyu Wang; Longjun Cai; Jianjun Zhang; Shaoqi Zhang (Scientific Reports)
Abstract Bladder cancer (BC) is notably prevalent, particularly among men. Emerging evidence highlights that traditional Chinese medicine (TCM) has distinct anticancer properties. This study focuses on recombinant MAP30, a key active constituent of Momordica charantia extract, recognized for its antiviral, immunomodulatory, and antitumor effects. We discovered that MAP30 suppresses BC cell proliferation and induces apoptosis in a dose-responsive manner. It also hinders cell migration, as evidenced by Transwell and wound healing assays. In nude mice, MAP30 injections adjacent to tumors significantly curtail tumor growth. Molecular analyses after MAP30 exposure show elevated SA-β-Gal activity and increased expression of cell cycle inhibitors p21 and p16 in BC cells. Integrating TCGA BC data, MAP30 appears to correct dysregulated gene expression associated with the cell cycle, senescence, apoptosis, and key pathways such as FOXO, TNF, and MAPK. Proteomic analysis identifies CENPA as a central molecule inhibited by MAP30. Correlation studies reveal CENPA’s significant association with oncogenic and immune-modulatory gene expression and immune cell infiltration. CENPA knockdown diminishes BC cell growth and motility, while its overexpression in MAP30-treated cells reverses these effects, suggesting CENPA’s pivotal role in MAP30’s anticancer activity and its potential as a therapeutic target. In conclusion, recombinant MAP30 effectively hampers bladder cancer cell proliferation and migration via CENPA downregulation and induces apoptosis and senescence, offering therapeutic potential against bladder cancer.